Composição de fitoquímicos e pigmentos em plantas de erva-mate cultivadas no Rio Grande do Sul - Londero, Chakira (2024)
Mate (Ilex paraguariensis A. St.-Hil) is a tree species, native to the American continent, with greater occurrence in Argentina, Brazil, and Paraguay. It has great cultural, environmental, and socioeconomic prominence. The leaves contain several bioactive compounds, which provide health benefits. The objective of this work was to evaluate the levels of phytochemicals and pigments in mate plants cultivated in the Rio Grande do Sul state. Leaf samples were collected from adult mate plants in 35 production units, distributed in the five recognized production regions (Nordeste Gaúcho, Missões/Celeiro, Alto Uruguai, Região dos Vales, and Alto Taquari). The collected leaves were dried in an oven with forced air circulation at 65ºC, until they reached a constant mass, and then crushed in a knife mill and sieved. To prepare the extract, 1g of the sample was weighed and dissolved in 50 ml of 70% alcohol solution. Total polyphenols were analyzed using the Folin Ciocalteu method. Absorbance readings were performed on a UV-visible spectrophotometer, at a wavelength of 765 nm for total polyphenols, and at a wavelength of 510 nm for total flavonoids. To determine chlorophylls a, b and total, and total carotenoids, the extract was diluted in a ratio of 1:20 (v/v extract: acidified extracting solution) and the absorbances were read at wavelengths 647, 663 and 470 nm, respectively. The data were subjected to analysis of variance and the means compared using the Scott-Knott test, at a level of 5%. There were significant differences among production regions for total phenolic compounds (from 181.82 to 1186.57* mg EAG.L-1), total flavonoids (from 5090.96 to 5660.80* mg CAT.L-1), and for total chlorophyll, and chlorophylls a and b, while for carotenoids, no significant difference was observed. Chlorophyll b concentrations were higher than those found for chlorophyll a considering all production regions. In general, the Nordeste Gaúcho and Região dos Vales stood out the most among the production regions. The results of this work show that the conditions of the mate cultivation regions of the Rio Grande do Sul State result in different concentrations of phytochemicals and pigments in the leaves, indicating the possibility of identifying some individuals that have greater commercial potential, aiming to the production of specific products.